KNOWLEDGE POWER MODEL ACCORDING TO MICHEL FOUCAULT ON NEWS TEXT THEMED CHANGES IN FUEL PRICES - ruhiman ruhiman; Rida Khamilawati; Rochmat Tri Sudrajat (IKIP Siliwangi, 2019)
The thought arises and develops based on the socio-cultural state of every human being, which then forms the distinctiveness of thought. Without realizing the thought of each individual has been monopolized by the ruler in a different sense. The ruler, in this case, as stated by Michel Foucault, that rationality and subjectivity of thought does not seem given and natural but are dominated by dominators who exploit some other people as a result of discourse. Gradually the influence of power has an impact on the ways of thinking and acting of dominant groups. One way that the ruling group built to strengthen the concept of